DAMPAK STRUKTUR KEPEMILIKAN SAHAM TERHADAP NILAI PERUSAHAAN: Studi Empiris pada Perusahaan Manufaktur Go Public di BEI Tahun 2010-2014 - Sapto Bayu Aji (Akademi Akuntansi YKPN Yogyakarta, 2017)
This study examined the effect of ownership structure on firm value in manufacturing companies. The study was based on 110 companies listed under the Indonesia Stock Exchange (BEI). The empirical analysis of the study was limited to a period of five years from 2010 to 2014. Variable analysis used in this study is the ownership of institutional and managerial ownership is used as independent variables while the value of the company used as the dependent variable. Data was analyzed using descriptive statistics and regression. The study results found that variable of institutional ownership and managerial ownership has a positive effect on firm value. Keywords: Corporate Values, Institutional Ownership, Managerial Ownership